Screening for Pseudomonas and Bacillus antagonistic rhizobacteria strains for the biocontrol of Fusarium wilt of chickpea - Hannane Abed; Noureddine Rouag; Dahou Mouatassem; Amar Rouabhi (Eurasian Journal of Soil Science, 2016)
The aim of this work is to study the ability of several isolates belonging to Rhizobacteria (Pseudomonas and Bacillus) collected from several chickpea growing areas in Algeria, to control the mycelium growth of Fusarium oxysporum f. sp. ciceris. Interesting isolates were characterized for their morphological characteristics, physiological and biochemical activities as potential bio-control agent. Fungal inhibition tests were performed using plate assay and each isolate were tested for the production of protease, cyanide hydrogen, indole acetic acid, antifungal volatile and extracellular compound. According to API 50 CH, we are able to identify six Bacillus species (B. subtilis, B. circulans, B. lentus, B. aneurinilyticus, B. firmus, B. licheniformis; and with API 20NE test we have identified three Pseudomonas species (P. aeruginosa, P. luteola, P. fluorescens). The ability of bacterial isolates was varied in production of Protease, Gelatinase, Amylase, Cellulase, Acid Indole acetic, Lipase, Catalase and Cyanid Hydrogen. This is traduced in different rate of inhibition growth due to various extracellular compounds, where B61 (Bacillus aneurinilyticus) and P39 (Pseudomonas luteola) and P70 (Pseudomonas fluorescens) were the most efficient with 77 and 55.5% respectively, while B39 (Bacillus firmus) and P41 (Pseudomonas luteola) were the most efficient by volatile compounds with 70.5 and 77.5% respectively. Our results indicate that these bacteria isolates can be used in the biocontrol of Fusarium oxysporum f. sp. ciceris.